Migration, economic crisis and adjustment in the UK - Clark, Ken; Drinkwater, Stephen; Robinson, Catherine (Bonn, 2014)
"We examine changes in migration to the UK in the period leading up to the Great Recession and in its immediate aftermath. In so doing, we pay particular attention to the changing countries of origin of recent migration flows to the UK, especially in relation to migration from other parts of the EU. The evolving patterns of migrants' socio-economic characteristics and labour market outcomes are also analysed, including how these relate to changes in the economy and migration policy. Finally, we review evidence on the impact of migration on the UK labour market and government finances."